Recovering disrupted social capital: insights from Lao PDR rural villagers' perceptions of local leadership - Jinho Kim; Ji-Hye Kim; Vanphanom Sychareun; Minah Kang (BMC, 2016)
Abstract Background Social capital is often believed to be one of the key prerequisites for successful implementation of community-based health programs. In less-developed countries, local leaders are positioned as major players in broad community health strategies and interventions, and their capacities and roles are expected to increase in prominence in future community-health-care promotions. In this study, we examined how local leaders' capacities could be related to social capital in rural villages in Lao PDR, and thus to villagers' willingness to participate in community-based health efforts. Methods We adopted a qualitative approach, conducting semi-structured interviews for both individuals and focus groups. In 2012, 103 people from six villages in the Khoun and Phoukoud districts participated in the interviews. For the individual interviews, we interviewed 22 mothers who had given birth in the past 5 years. For the focus groups, we interviewed 30 women (six groups), 30 men (six groups), and 21 senior villagers (five groups). Results First, we noted large variations in the levels of community social capital across villages: four out of six study villages showed a high level of social capital, while two villages suffered greatly from a low level of social capital. In search of the reasons for the disrupted social capital in the latter two villages, interviews revealed that failed leadership, especially in regard to local resource allocations-lack of transparency and corrupt practices-were commonly cited reasons for disrupted social capital. The data also showed that the villagers' mistrust of these failed local leaders critically reduced their willingness to participate in community-based health efforts, and especially in those that involved resource mobilization and risk-sharing for healthcare. Finally, we found that good communication skills and participatory decision-making styles were attributes that rural villagers in Lao PDR expected of their local leaders. Conclusion This study suggests that failed local leadership is detrimental to community participation, resource mobilization, and building communities' social capital. To achieve intended health care goals through community-based interventions, there is a need to first support local leadership at all levels through capacity-building and improved communication within communities.